2021
DOI: 10.1111/ijpo.12824
|View full text |Cite
|
Sign up to set email alerts
|

Associations between weight status, body satisfaction, ethnic identity and self‐esteem in Oceanian adolescents

Abstract: Summary Background Self‐esteem has consistently been observed to be relatively low in adolescents with obesity. In the Pacific region, the prevalence of obesity in adolescence is high, but few studies have considered issues of self‐esteem in this population. Objective To examine associations between weight status, body dissatisfaction and self‐esteem in a sample of New Caledonian adolescents and to test for moderation effects of ethnicity on predictors of self‐esteem. Methods Objective anthropometric measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…In its parent form [ 45 ] and in a range of national groups [ 49 ], MEIM-R scores have been found to consist of two factors indexing exploration of, and commitment towards, one’s ethnic group. However, among New Caledonian adolescents, MEIM-R scores have been found to reduce to a single dimension consisting of all 6 items [ 42 ]. We, therefore, computed an overall score as the mean of all 6 items, with higher scores reflecting greater affiliation with one’s ethnic group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In its parent form [ 45 ] and in a range of national groups [ 49 ], MEIM-R scores have been found to consist of two factors indexing exploration of, and commitment towards, one’s ethnic group. However, among New Caledonian adolescents, MEIM-R scores have been found to reduce to a single dimension consisting of all 6 items [ 42 ]. We, therefore, computed an overall score as the mean of all 6 items, with higher scores reflecting greater affiliation with one’s ethnic group.…”
Section: Methodsmentioning
confidence: 99%
“…We, therefore, computed an overall score as the mean of all 6 items, with higher scores reflecting greater affiliation with one’s ethnic group. Frayon and colleagues [ 42 ] reported that the MEIM-R had adequate composite reliability. In the present study, McDonald’s omega scores was 0.74 (95% CI 0.70, 0.78).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coopersmith (1967) menyatakan bahwa salah satu landasan utama dalam self-value (salah satu aspek harga diri) yaitu apabila seseorang memiliki pandangan bahwa dirinya berharga dan penting. Self-esteem rendah juga dapat menyebabkan hambatan pada manajemen berat badan dan kegagalan untuk mengontrol berat badan (Frayon et al, 2021), maka dapat disimpulkan bahwa hal ini memiliki hubungan satu sama lain.…”
Section: Pembahasanunclassified